Professionals who exercise care in childhood residential institutions: an integrative review (Research, Society and Development, 2023)
It is known that care influences several aspects of human development. In general, it is excercised by the parents, however, in cases of institutionalization, the reception is carried out by professional caregivers, who become a reference for the children and adolescents assisted there. In this way, the objective was to know what has been published about caregivers and their role in child and youth care institutions. This is an integrative review that gathered 11 articles published between 2011-2021, for the search, the descriptors caregiver and host were used in Portuguese, English and Spanish and the databases Lilacs, Psychology Index and Sage Journals databases. Based on the analysis of studies, three subtitles were listed: Affective bonding as a form of care for institutionalized children and adolescents; daily care for institutionalized children and adolescents; and weaknesses experienced in the care process for institutionalized children and adolescents. It was concluded that caregivers play an extremely important role in the lives of children and adolescents, but they feel insecure and psychologically helpless to perform their duties. The need for further studies on the subject is highlighted, as a way of contributing to the development of training and public policies that support this process.